2002
DOI: 10.1016/s0006-2952(02)00839-0
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent induction of Fas and apoptosis in leukemic cells by an adenosine derivative, Cl-IB-MECA

Abstract: A 3 adenosine receptor (A 3 AR) agonists have been reported to influence cell death and survival. The effects of an A 3 AR agonist, 1- [2-chloro-6-[[(3-iodophenyl)methyl]amino]-9H-purin-9-yl]-1-deoxy-N-methyl-β-D-ribofuranonamide (Cl-IB-MECA), on apoptosis in two human leukemia cell lines, HL-60 and MOLT-4, were investigated. Cl-IB-MECA (≥30 μM) increased the apoptotic fractions, as determined using fluorescence-activated cell sorting (FACS) analysis, and activated caspase 3 and poly-ADP-ribose-polymerase. Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 41 publications
8
41
1
Order By: Relevance
“…Previous studies have demonstrated that activation of A 3 AR by the compound can exert signifi cant inhibitory effects on the in vitro and in vivo growth of different tumor cell types [11,19,20] . In addition, the presence of functional A 3 AR in HL-60 cells has been reported [15][16][17] , and, in the present study, comparable amounts of A 3 AR mRNA were found in HL-60 and HL-60R cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have demonstrated that activation of A 3 AR by the compound can exert signifi cant inhibitory effects on the in vitro and in vivo growth of different tumor cell types [11,19,20] . In addition, the presence of functional A 3 AR in HL-60 cells has been reported [15][16][17] , and, in the present study, comparable amounts of A 3 AR mRNA were found in HL-60 and HL-60R cells.…”
Section: Discussionsupporting
confidence: 84%
“…The occurrence of A 3 AR in HL-60 cells has previously been reported [15][16][17] . We compared the expression of A 3 AR mRNA in HL-60 and HL-60R cells by RT-PCR.…”
Section: Expression Of a 3 Ar In The Cellsmentioning
confidence: 78%
“…Earlier studies demonstrated that A3AR agonists such as IB-MECA or Cl-IB-MECA, at micromolar concentrations, induced apoptosis in different cell types. In some of the studies, the activity was found to be A3AR-mediated, whereas in others, A3AR antagonists did not counteract the effect, demonstrating that the apoptosis was not A3AR-mediated (27,28). In distinction from these studies, in the present work, IB-MECA was used at nanomolar concentrations, and its activity was counteracted by the antagonist MRS 1523, demonstrating that the response was A3AR-dependent.…”
Section: Ib-meca Modulates Key Elements Downstream To A3arcontrasting
confidence: 46%
“…We now speculate that desensitization/down-regulation of the A 3 AR under such agonist exposure conditions is indeed at the basis of cytoprotection. This implies a causative role for this receptor subtype in induction of cell death, as nevertheless suggested by data obtained in different experimental models (Shneyvais et al, 1998;Appel et al, 2001;Kim et al, 2002).…”
Section: Downloaded Frommentioning
confidence: 76%